2009
DOI: 10.1007/s11071-009-9589-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear vibration of variable speed rotating viscoelastic beams

Abstract: Non-linear vibration of a variable speed rotating beam is analyzed in this paper. The coupled longitudinal and bending vibration of a beam is studied and the governing equations of motion, using Hamilton's principle, are derived. The solutions of the non-linear partial differential equations of motion are discretized to the time and position functions using the Galerkin method. The multiple scales method is then utilized to obtain the first-order approximate solution. The exact first-order solution is determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In addition, the early research that focused on the problem of rotating nonconstant speed was done in the work by Kammer and Schlack (1987). Nonlinear vibration of a variable speed rotating beam was studied by Younesian and Esmailzadeh (2010), where the influence of various parameters was investigated. The nonlinear dynamic response of a rotating blade with varying rotating speed was investigated by Yao et al (2012), and the results showed that the dynamic responses of the rotating blade changed from periodic motions to chaotic motions with different rotating speeds.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the early research that focused on the problem of rotating nonconstant speed was done in the work by Kammer and Schlack (1987). Nonlinear vibration of a variable speed rotating beam was studied by Younesian and Esmailzadeh (2010), where the influence of various parameters was investigated. The nonlinear dynamic response of a rotating blade with varying rotating speed was investigated by Yao et al (2012), and the results showed that the dynamic responses of the rotating blade changed from periodic motions to chaotic motions with different rotating speeds.…”
Section: Introductionmentioning
confidence: 99%
“…The linear natural frequencies of beams that rotate with constant speed were investigated by many researchers, for example in [1][2][3][4][5]. Works that consider geometrically nonlinear models of rotating beams may be found, for example [6][7][8]. In what concerns modern wind turbine blades, most of them are constructed with load carrying box girder inside the blade and shells on the surface of the blade [9].…”
Section: Introductionmentioning
confidence: 99%
“…Dasa et al [14] investigated the free out-of-plane vibration of a rotating beam with a non-linear spring mass system using a perturbation method. The non-linear coupled longitudinal and bending vibration of a variable speed rotating beam was modelled by Younesian and Esmailzadeh [15]. The solution of the nonlinear partial differential equation of motion was assumed to be a series of multiplications of time and position functions in accordance with the Galerkin modal summation technique.…”
Section: Introductionmentioning
confidence: 99%